AN EVALUATION OF SUMMER DISCOMFORT IN NIŠ (SERBIA) USING HUMIDEX - Lukić, Milica; Pecelj, Milica; Protić, Branko; Filipović, Dejan (Journal of the Geographical Institute “Jovan Cvijić” SASA, 2019)
The bioclimatic analysis of the central area of the city of Niš conducted in this paper is based on the use of the bioclimatic index Humidex, which represents subjective outdoor temperature that one feels in warm and humid environment. The purpose of this research is to observe the index change on a daily basis during the hottest part of the year (June, July, and August) over the period from 1998 to 2017. For the purposes of this analysis, hourly (7:00, 14:00), maximum and mean daily values of meteorological parameters (air temperature and relative humidity) were used, for the period of 20 years (1998–2017), which were measured at Niš weather station (43°19’N, 21°53’E, at an altitude of 202 meters). The findings indicate a gradual change in the bioclimatic characteristics of this area during this period, especially over the last decade. After 2007 there has been a decrease in the total number of the days described as “comfortable”. However, there has been an increase in the index values in all the other heat stress categories characterized by a higher or lower degree of thermal discomfort. The years 1998, 2000, 2003, 2007, 2011, 2016, 2015, and 2017 stand out as adverse years.